Immunological and molecular study of Chlamydia trachomatis as causative agent of abortion in Al-Muthanna province - Al-Nuaimy, Wafaa Ayad; Al-Jandeel, Tareq Jafaar (The Iraqi Journal of Veterinary Medicine, 2022)
Chlamydiasis during pregnancy should be considered a significant risk factor for adverse pregnancy outcomes in humans. 120 women who had a single or repeated abortion were selected for this study, and they were referred with a physician report for TORCH tests to determine the final diagnosis of pregnancy loss. The control were (40) healthy pregnant women with a history of a normal pregnancy. The innate immunity in abortive women was higher than normal pregnancies, that was estimated by Nitroblue Tetrazolium test done to estimate the phagocytic activity, there was a significant increase (P=0.009) in phagocytic activity in the leukocytes of abortive women which was (22%) higher than that in control. Also, the cellular immune response was higher in abortive women than that in control. Methyl Thiazolyl Tetrazolium assay was performed to estimate lymphocyte transformation index of peripheral blood leukocytes in abortive women. The results of Methyl Thiazolyl Tetrazolium assay showed a significant increase (P=0.001) in the lymphocyte transformation index in the lymphocytes of abortive women which was (27%) higher than control. The serological detection by ELISA showed that anti-C. trachomatis IgG was (14.2%), and the molecular detection by Quantitive Real Time-Polymerase Chain Reaction showed positive results (17.5%) of total abortive women. The present study demonstrated a high level of relationship between C. trachomatis and abortion among women in the study samples. The age group (20-25years) was the most susceptible to chlamydial infection and the infection was higher in recurrent miscarriages than in single miscarriage.